P160 Utility of HPV genotyping and cytology to predict cervical intraepithelial grade 2 outcome after 2 years of follow-up. (1st November 2019) - Salvadó Salvadó, A; Miralpeix Rovira, E; Gayete Lafuente, S; Kajou Auge, N; Castells, M; Solé Sedeño, JM; Mancebo Moreno, G
Abstract : Introduction/Background: Cervical intraepithelial neoplasia (CIN) commonly occurs in women of reproductive age. Conservative management of CIN1 is widely established, as is excisional treatment for CIN3; however, management of CIN2 remains debatable. Our objective was to evaluate the utility of human papilloma virus (HPV) genotyping and the previous cytology in the management of patients with CIN2 lesions. Methodology: Patients newly diagnosed with CIN2 cervical biopsy, older than 16 years old, who agreed to follow up every 6 months for at least 2 years, were prospectively recruited. Unsatisfactory colposcopy and endocervical CIN2 were considered exclusion criteria. Total regression was defined as two consecutives negative cytologies and no evidence of colposcopic lesions, partial regression if final biopsy showed CIN1, persistence when biopsy showed CIN2, and progression if a CIN3 biopsy was detected during follow-up. Results: The mean age of 300 patients included was 30 years, 50% were smokers, 76% nulliparous, 9% were vaccinated, 6% were pregnant at moment of diagnosis and 37% affected by HPV16. Overall, the rate of spontaneous total regression at 2 years of follow-up was 59.7%, 20.9% presented partial regression, 13.1% had persistent disease, while 6.3% progressed. HPV16 infection [OR 4.7 (95% CI 1.6 to 13.7)] and previous HSIL cytology [OR 4.4 (95% CI 1.5 to 12.8)], were statistically associated with progression. Age or smoking were no statistically associated.None of vaccinated patients neither HPV-HR negative lesions progressed in 24 months. Conclusion: The high regression rate of CIN2 supports clinical observation and conservative management in selected patients. Patients with CIN2 lesions HPV16 positive and HSIL previous cytology are more likely to progress to CIN3, so tight control is crucial. In contrast, vaccinated patients and HPV-HR negative lesions regress spontaneously. Study of predictive factors of CIN2 evolution, as HPV16 or previous cytology, would have a great clinical value to reduce unnecessary cone excision and tailored treatment. Disclosure: The authors declare no conflicts of interest. None received grant support for the study neither for other clinical or research activity, except for the inscription to the current congress, for three of the authors, that was funded by VIFOR Pharma (non related to the study we present).